Het magisch realisme in enkele recente Afrikaanse romans - van Coller, H.P. (Zakład Studiów Niderlandzkich i Południowoafrykańskich, Wydział Anglistyki UAM / Wydawnictwo Naukowe Exemplum, 2006)
Realism, with the implication that it amounts to “true” representation, is one of the most important classification principles in traditional Afrikaans literary historiography. Recent historiographical approaches and theories undermine traditional mimetic beliefs, thus also traditional realism. Nowadays readers are to be persuaded of a possible reality by virtue of the array of verbal elements and not necessarily by “realistic” features. In magic realist texts two oppositional systems clash, whilst each tries to create a fictional world. In this preoccupation with “images of borders and centres” reality is presented as neither fixed nor stable. Magic realist texts are therefore especially suited to represent a colonial past, eg. South African history and to undermine its master discourses by giving voice to discarded petites histoires. In conclusion to this article two novels by prominent Afrikaans writers are discussed as illustration of the thesis that a realistic representation is not sufficient to portray South Africa and its complexities.